Effects of surfactants on the formation of gelatin nanofibres for controlled release of curcumin - Deng, Lingli; Kang, Xuefan; Liu, Yuyu; Feng, Fengqin; Zhang, Hui (Food chemistry, 2017)
•Curcumin was encapsulated within the gelatin nanofibre.•Surfactants affect the morphology of gelatin nanofibre.•Surfactants modulate the release behaviour, antioxidant and antimicrobial activities of curcumin. This work studied the effects of non-ionic Tween 80, anionic sodium dodecyl sulfonate (SDS) and cationic cetyltrimethyl ammonium bromide (CTAB) surfactants on the morphology of electrospun gelatin nanofibres, and on the release behaviour, antioxidant activity and antimicrobial activity of encapsulated curcumin. Scanning electron micrographs showed that addition of SDS significantly increased the nanofibre diameter. Fourier transform infrared and differential scanning calorimetry analysis indicated that gelatin and SDS intimately interacted via electrostatic and hydrophobic interactions. However, these interactions inhibited the release of curcumin from the nanofibres with SDS, while CTAB and Tween 80 both facilitated the release. SDS and Tween 80 showed protective effects on curcumin from the attack of 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radicals, and the increased release of curcumin from nanofibres with CTAB or Tween 80 resulted in a higher reducing power. The antimicrobial activity results suggested that the curcumin encapsulated gelatin nanofibres with CTAB exhibited effective inhibition against Staphylococcus aureus.